Analysis of The Utilization of CNC Machines For Increasing Productivity of Timber Businesses in Guli Village Boyolali District - Poerwanto, Eko; Hariyanto, Kris (SENATIK STT Adisutjipto, 2020)
The village of Guli has been carrying out timber industry activities for a long time, more than 14 years. Products from the timber industry in Guli village today: furniture, frames and doors. These production activities have used quite advanced mechanical equipment, but the products produced are still very standard, there is no art / art touch that can increase the selling value of the products produced. This research uses descriptive method, which describes the theory of productivity and develops it in the concept of a community empowerment program in Guli village. The research results are expected to increase the productivity of the Guli village timber industry by applying the Guli village resource development program through the Guli Village Posyantek, so that the empowerment of Guli village youth will occur and it is hoped that it will increase Bumdes assets. This empowerment program does not change the structure of the timber business that has been run by the people of Guli village.